An interface protection system based on an embedded metrology system platform. (December 2021) - Artale, Giovanni; Caravello, Giuseppe; Cataliotti, Antonio; Cosentino, Valentina; Di Cara, Dario; Guaiana, Salvatore; Panzavecchia, Nicola; Tinè, Giovanni
Abstract: The aim of this work is to present an interface protection system (IPS) for Distributed Generators (DG) and Energy Storage Systems (ESS). The new prototype of IPS guarantees standard protection requirements, in terms of both voltage and frequency measurement accuracies and trip times. Moreover, it has the additional functionalities of implementing a communication link between the Distribution System Operator (DSO) and the DG and ESS Inverter. The new IPS is based on a smart meter platform with an integrated power line communication modem. Moreover, it has also an integrated metrology section. Experimental tests will show how this last feature allows a significant reduction of the measurement data access time allowing an improvement of trip time accuracy.